Production of nepheline/quartz ceramics from geopolymer mortars - Kuenzel, C.; Grover, L. M.; Vandeperre, Luc; Boccaccini, Aldo R.; Cheeseman, C. R. (Journal of the European Ceramic Society, 2013)
This research has investigated the mechanical properties and microstructure of metakaolin derived geopolymer mortars containing 50% by weight of silica sand, after exposure to temperatures up to 1200°C. The compressive strength, porosity and microstructure of the geopolymer mortar samples were not significantly affected by temperatures up to 800°C. Nepheline (NaAlSiO 4) and carnegieite (NaAlSiO 4) form at 900°C in the geopolymer phase and after exposure to 1000°C the mortar samples were transformed into polycrystalline nepheline/quartz ceramics with relatively high compressive strength (∼275MPa) and high Vickers hardness (∼350 HV). Between 1000 and 1200°C the samples soften with gas evolution causing the formation of closed porosity that reduced sample density and limited the mechanical properties. © 2012 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.produc
Keywords: A. Sintering; C. Mechanical properties; Ceramic; Final microstructure; Geopolymer